2020
DOI: 10.1002/slct.201904630
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance and Characterization of Highly Efficient Composite Ni(Clx)/CeO2/η‐Al2O3/FeCrAl Wire Mesh Catalysts for Preferential CO Methanation

Abstract: Structured composite Ni(Cl x )/CeO 2 /η-Al 2 O 3 /FeCrAl catalysts are developed for the reaction of preferential methanation of carbon monoxide in the presence of carbon dioxide. The use of a FeCrAl alloy wire mesh as a support for Ni(Cl)/CeO 2 allows preparation of a heat-conducting catalyst that is similar in performance and physical-chemical properties to the highly efficient catalysts in the form of micro pellets, as confirmed by catalytic tests and XRD, XPS, TEM, SEM, EDX characterization techniques. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In the high-resolution spectrum of the Cl 2p peak (Fig. 1d) for Cl 32 –Ni(OH) 2 , chlorine anions mainly exist in the form of Ni–Cl bonds, 32 indicating that chlorine anions replace OH − in the hydroxide layers. It is because the concentration of Cl − in saturated NaCl solutions is 123 times higher than that of OH − (about 6.15 mol L −1 vs. 0.05 mol L −1 ), which can replace partial OH − and bond with Ni during the precipitation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the high-resolution spectrum of the Cl 2p peak (Fig. 1d) for Cl 32 –Ni(OH) 2 , chlorine anions mainly exist in the form of Ni–Cl bonds, 32 indicating that chlorine anions replace OH − in the hydroxide layers. It is because the concentration of Cl − in saturated NaCl solutions is 123 times higher than that of OH − (about 6.15 mol L −1 vs. 0.05 mol L −1 ), which can replace partial OH − and bond with Ni during the precipitation process.…”
Section: Resultsmentioning
confidence: 99%
“…Deionized water was used throughout all of the experiments. 16,24,32,40) and Ni(OH) 2 A facile one-step coprecipitation method was employed to synthesize Cl 32 -Ni(OH) 2 catalysts. In a typical preparation process, a certain weight of NaCl (32 g) was dissolved into 80 ml of deionized water in a 250-ml beaker and stirred for 1 h. Then, 2 g of Ni(NO 3 ) 2 Á6H 2 O was added to the solution under vigorous magnetic stirring and kept stirring for another 5 h. After that, 300 mL NH 3 ÁH 2 O was added to the mixed solution drop-wise.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…The Cl content from the X‐ray photoelectron spectroscopy (XPS) is ≈6 at% (Figure 1f and Figure S5, Supporting Information). By deconvolution the XPS Cl 2p peak (Figure 1g), Cl atom mainly exists in the form of Ni/CoClCl bond, [ 29 ] indicating Cl – replaces OH – in the hydroxide layers (denoted as Ni/Co–OH). It is because the concentration of Cl – in saturated NaCl solutions is 123 times higher than that of OH – (about 6.15 mol L –1 vs 0.05 mol L –1 ), which can replace some of OH – and contact with Ni or Co during co‐precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…4c and d). 42,43 In 4e). It can be concluded that the binding of metal atoms in the hydroxide layer is more stable when N, Cl ions are located on both sides above and below the Ni atom.…”
Section: Electrochemical Performancementioning
confidence: 98%
“…In addition, Cl ion substitution also changes the electronic configuration of Ni and Co, which enhances the electrical conductivity and redox activity. 43 According to the above results, the reactive formula of the NCSeO-NCl-NiCC electrode can be speculated as follows: 40…”
mentioning
confidence: 98%